ICSID 2013 Annual Report - International Centre for Settlement of Investment Disputes (Washington, DC, 2014)
International investment law and international investment arbitration are relatively new disciplines: the first bilateral investment treaty was signed by Pakistan and Germany in 1959, the first investment treaty offering investor-state arbitration was concluded in 1968 between the Netherlands and Indonesia, the first International Center for Settlement of Investment Dispute (ICSID) case was registered in 1972, and the first treaty-based investment case was registered by the Centre in 1987. The Centre itself was established in 1966, along with the coming into force of the ICSID convention. It was the first dispute resolution facility designed exclusively for international investment dispute settlement, and it continues to be the only international facility dedicated to this area. This specialized mandate has allowed ICSID to develop an unparalleled expertise and focus, which benefits disputing parties, arbitrators and contracting states. Cumulatively, ICSID has administered over 430 cases, involving foreign investors from all regions of the world and more than 95 states and state agencies under the ICSID convention and rules. In addition, it has administered over 40 investment arbitration cases initiated under the United Nations Commission on International Trade Law (UNCITRAL) arbitration rules and other arbitral rules. The end-of-fiscal year results confirm that ICSID remains the leader in international investment dispute resolution. This report is organized as follows: chapter one gives introduction; chapter two gives list of contracting states and other signatories of the convention; chapter three presents panels of arbitrators and of conciliators; chapter four gives operations of the Centre; chapter five presents outreach of ICSID; chapter six deals with forty-sixth annual meeting of the administrative council; and chapter seven presents financial statements of ICSID.